HETEROSUBTYPIC IMMUNE RESPONSE AND CROSS-PROTECTION AGAINST A HIGHLY PATHOGENIC A (H5N1) INFLUENZA VIRUS IN MICE IMMUNIZED WITH COLD-ADAPTED A/LENINGRAD/134/17/57 (H2N2) INFLUENZA VIRUS - A. R. Rekstin; J. A. Desheva; X. Lu; G. I. Alexandrova; A. I. Klimov; J. M. Katz; L. G. Rudenko (Медицинская иммунология)
While investigating the efficacy of an H5N2 ca reassortant vaccine candidate in protecting against a lethal challenge with a highly pathogenic (HP) H5N1 virus in the mouse model, we observed a degree of cross-protection provided by the ca Len/17 (H2N2) virus itself. 80% of mice administered a high dose of attenuated Len/17 vaccine intranasally (i.n.) survived after a lethal challenge with A/Hong Kong/483/97 H5N1 virus. Therefore, we investigated the basis of the cross- reactive immunity between H2N2 and H5N1 viruses that may have contributed to recovery from lethal HK/ 483 virus infection. Sera from mice immunized i.n. with Len/17 did not cross-react with HK/483 virus in neutralization or hemagglutination-inhibition assays, however IgG and IgA antibodies that cross-reacted with the hemagglutinin and neuraminidase of H5N1 1997 viruses were detected. Spleen cells from mice immunized i.n. with Len/17 vaccine showed enhanced production of IL-2, IL-4, IL-5, IL-10, and IFNγ following in vitro stimulation with inactivated H5N1 virus. Our findings indicate that both cross-reactive humoral and cellular immunity induced by Len/17 H2N2 vaccine may plays a role in recovery from lethal H5N1 virus infection. A better understanding of the mechanisms of heterosubtypic immunity will improve vaccine design against HP avian influenza viruses.